IMPROVING THE EDUCATIONAL PROCESS IN THE DISCIPLINE OF DESIGN THEORY OF FINE ARTS AND ENGINEERING GRAPHICS REQUIREMENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2026)
The article considers the issues of improving teaching within the framework of design theory, the use of integrated pedagogical methods and modern technologies, and the development of creative thinking. The importance of technical training and aesthetic approaches is emphasized.